PENGARUH ALOKASI WAKTU PEMBELAJARAN BAHASA INDONESIA TERHADAP MINAT BELAJAR SISWA SMK - Nurhasani Cantika Dewi; Windaningsih Windaningsih; Teti Sobari (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research was motivated by the lack of enthusiasm of students when learning Indonesian in the afternoon, resulting in a large number of activities carried out by students outside of learning. This scientific article has the intention to see the effect of time allocation on students' interest in learning Indonesian learning in class X of SMK Informatics Fithrah Insani. This study uses descriptive qualitative methods. The research technique uses open and closed questionnaire techniques and observation by observing objects directly. All students of SMK Informatika Fithrah Insani were chosen as the population. Class X as many as 46 students were taken into the study sample. The researcher proposed a problem statement as follows 1) whether there was an effect of time allocation on students' learning interest in learning Indonesian. The results of the research prove that the allocation of time for Indonesian language learning given at the last hour influences students' interest in learning Indonesian.